Perancangan Ulang Identitas Visual Komunitas Kesehatan Mental Halo Jiwa Indonesia - Andira, Ayu; Septian Rachman, Vicky (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2022)
The establishment of the Halo Jiwa Indonesia community was motivated by the issue of mental health in Indonesia, which is still not highlighted by the public and the government. One of Halo Jiwa Indonesia's visual identities is found in the logo. Judging from the analysis of the data that has been obtained from the results of interviews and observations, currently the Halo Jiwa Indonesia community does not have a fixed visual identity, thus it is hard to describe the characteristics of the community among similar communities. By conducting a literature study to build the visual identity of the Halo Jiwa Indonesia community, this paper describes the process of redesigning the visual identity for the Halo Jiwa Indonesia community.